Os Centros de Atenção Psicossocial Infantojuvenis (CAPSi) e as práticas de cuidado para as crianças e adolescentes em intenso sofrimento psíquico - Taño, Bruna Lídia (Universidade Federal de São Carlos, 2014)
Until the last decades, the actions of mental health care in children and adolescents in Brazil have been put in philanthropic actions based on sheltering, what leaded to violent practices and subjection. From the establishment of the SUS (Unified Health System) and the elaboration of the Children and Adolescents Statute, it became possible to resize the care and attention disposed to that population, providing them the right to citizenship and the expression of their wishes and needs. In 2001, there is the creation of the Youth and Adolescents Psychosocial Care Centers (in Portuguese, Centros de Atenção Psicossociais Infantojuvenis CAPSi), responsible for caring of children and adolescents in intense psychic suffering, with a communitarian and territorial focus, in substitution to the sheltering models which had focus on coercion and restriction. Recent studies suggest that, although the CAPSi are the reference services on situations of intense suffering in children and adolescents, the offerings of attention and caring are still short of the needs of subjects and their families. In this direction, the present study aims to identify the caring practices developed at CAPSi for children and adolescents in intense psychic suffering from the view of technicians who act in these services and of relatives/tutors of the children and adolescents inserted in these services. Participated of the study 17 technicians and 16 relatives/tutors, from four CAPSi: three of them in the Metropolitan São Paulo and one in the countryside of the state. The data was collected from semi structured interviews realized with the technicians and relatives/tutors, as well as identification sheets for characterization of the CAPSi and the children/adolescents and his relatives participating in the study. To the obtained material, we proceeded with analysis using the Collective Subject Speech technique (in Portuguese, Discurso do Sujeito Coletivo DSC) to the interviews and categorization and descriptive presentation to the identification sheets. The main results indicate that the CAPSi have been attending a greater population then expected by the normative and, despite of what these normative indicate, a greater contingent of users are attended weekly in the services. The users in intense psychic suffering are destined mainly to individual sessions, followed by spaces of coexistence. The professionals recognize that the most effective actions of caring to the populations in greater psychic suffering are the approaches to relatives and tutors. The relatives related different ways of insertion in the CAPSi, from participation in therapeutic groups to no activity at all. We discuss the presence of multiple perspectives present in the understanding of the experience of psychic suffering in children and adolescents and their families, who don t find substantial resonance in the practices realized in the services still massively realized in an outpatient way as a possible reflection of the institutional difficulties experienced by the workers. These observations point to a need of reorganization of the attention in the CAPSi in such way to include the families in the treatment actions and on the spaces of social role as well as the importance of amplification of offerings of inventive and singular actions to the subjects in intense psychic suffering.
Keywords: Serviços de saúde mental; Políticas públicas; Criança; Adolescentes; Mental health services; Public policies; Child; Adolescent; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL